Evaluation of MRI Findings in Patients with Chronic Primary Headache - Amarjit Kaur; Dimple Mittal; Navkiran Kaur; Ishita Gupta; Simranjeet Singh (Asian Journal of Medical Radiological Research, 2020)
Background: Headache is a common clinical feature in patients in the emergency room and in general neurology clinics. Hence; under the light of above mentioned data, we planned the present study to assess the role of MRI scan in persons with chronic) primary headache. Subjects and Methods: The present study included 26 patients with chronic primary headache. Relevant history, clinical examination and routine investigations were done. Patients underwent MRI investigations. The entire patient diagnosed with non-acute headache was included in the study irrespective of their age and gender informed written consent was taken from all the patients. Imaging was performed using a head coil with patient in a supine position. All the MR imaging examination were performed on a Seimen’s Avento 1.5 Tesla Magnet MR system, slice thickness was 4-5mm with an inter slice gap of 0.5mm. MR imaging findings were compiled as per proforma and subjected to analysis using SPSS software. Results: Significant MRI findings were found to be present in 23.08 percent of the patients. Out of 15 migraine patients, significant abnormal MRI findings were present in 26.67 percent of the patients. Out of 6 patents with tension type headache, significant abnormal MRI findings were found to be present in 1 patient only (16.6 percent). Among the 5 patients with cluster headache, significant abnormal MRI findings were found to be present in 1 patient (20 percent). Conclusion: The chance of finding a significant underlying abnormality in patients with a stable headache pattern and a normal neurological examination is uncommon but if red flags are present neuro-imaging must be strictly considered.